Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T17:27:39+01:00
A) 2x + 6 = 20
2x=20-6
2x=14/:2
x=7

b) 23 + 9y = 50
9y=50-23
9y=27/:9
y=3

c) 8y- 36 = 24
8y=24+36
8y=60/:8
y=7,5

d) -4c - 46 = -2
-4c=-2+46
-4c=44/:(-4)
c=-11

e) 13 + 2x +3
2x=-16/:2
x=-8

f) -7 = 5x + 1
5x+1=-7
5x=-8
x=-8/5

g) 7x - 21 = 5x
7x-5x=21
2x=21/:2
x=10,5

h) 6y - 13 = -52
6y=-52+13
6y=-39/:6
y=-6,5

i) 4x - 4 =3
4x=3+4/:7
x=7/4

j) 3c + 2 = -70
3c=-70-2
3c=-72
c=-24

k) 33 - 4x = 4x
-4x-4x=-33
0=-33
równanie sprzeczne

l) 5 - 10x = -2x
-10x+2x=-5
-8x=-5/:(-8)
x=5/8

2009-11-19T17:28:50+01:00
A) 2x + 6 = 20
2x=14/:2
x=7
b) 23 + 9y = 50
9y=27/:9
y=3
c) 8y- 36 = 24
8y=60/:8
y=7,5
d) -4c - 46 = -2
-4c=44/:-4
c=-11
e) 13 + 2x +3
wydaje mi sie że po 13 powinno być =
13=12x+3
12x=-10/:12
x=-0,83
a jeśli nie to napisz wiadomośc
f) -7 = 5x + 1
-6=5x/:5
-6/5=x
g) 7x - 21 = 5x
2x=21/:2
x=10,5
h) 6y - 13 = -52
6y=-39/:6
y=-6,5
i) 4x - 4 =3
4x=7/:4
x=7/4
j) 3c + 2 = -70
3c=-72/:3
c=-24
k) 33 - 4x = 4x
8x=33/:8
x=4,125
l) 5 - 10x = -2x
-8x=-5/:-8
x=5/8
2009-11-19T18:04:28+01:00
A)2x + 6 = 20
2x=20-6
2x=14/:2
x=7

b) 23 + 9y = 50
9y=50-23
9y=27/:9
y=3
c) 8y- 36 = 24
8y=24+36
8y=60/:8
y=7.5

d) -4c - 46 = -2
-4c=-2+46
-4c=44/:-4
c=-11

f) -7 = 5x + 1
-5x=7+1
-5x=8/:(-5)
x= -1.3
g) 7x - 21 = 5x
7x-5x=21
2x=21/:2
x=10,1
h) 6y - 13 = -52
6y=-52+13
6y= -39/:6
y= - 6,5
i) 4x - 4 =3
4x=3+4
4x=7/:4
x=1,3
j) 3c + 2 = -70
3c=-70-2
3c=-72/:3
c=-24
k) 33 - 4x = 4x
-4x-4x=-33
-8x=-33/:(-8)
x=4,1
l) 5 - 10x = -2x
-10x+2x=-5
-8x= -5/: (-8)
x= ⁵₈